(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The research under consideration is how to build COL (Component Organised Learning) based curriculum lifecycle that teachers can apply in different fields. The problem is that the degree studies curriculum is not always applied to working students as the needs of the companies they work for differ. Companies find it more valuable when students can use the existing curriculum topics to solve today's company problems. Current degree studies take considerable time and are unsuitable for full-time employed specialists. The proposed Education 4.0 concept brings the knowledge and skills required by the market for full-time employed students in a time-efficient way. One possible solution to apply this concept in practice is to create a micro-credential curriculum for companies. The authors suggest using the intensive week approach for analysis, where the students will solve the real company problem using previously studied solutions. They will also use the Moodle courses linked to the developed COL to speed up access to the materials. Authors suggest organising such an event in collaboration with consortium partners and involving all teaching staff who worked on course development. After introducing problems brought by the company and visiting the company on site, asking the questions, students define the task to be solved in groups. After that, the Authors recommend providing intensive courses where each partner will present the developed Moodle materials. The target is that the students will solve the problem in 24h and present solutions to the company representative.